In Vitro Evaluation of Antiviral Activities of Funicone-like Compounds Vermistatin and Penisimplicissin against Canine Coronavirus Infection - Claudia Cerracchio; Maria Michela Salvatore; Luca Del Sorbo; Francesco Serra; Maria Grazia Amoroso; Marina DellaGreca; Rosario Nicoletti; Anna Andolfi; Filomena Fiorito (MDPI AG, 2023)
Recent studies have demonstrated that 3-O-methylfunicone (OMF), a fungal secondary metabolite from Talaromyces pinophilus belonging to the class of funicone-like compounds, has antiviral activity against canine coronaviruses (CCoV), which causes enteritis in dogs. Herein, we selected two additional funicone-like compounds named vermistatin (VER) and penisimplicissin (PS) and investigated their inhibitory activity towards CCoV infection. Thus, both compounds have been tested for their cytotoxicity and for antiviral activity against CCoV in A72 cells, a fibrosarcoma cell line suitable for investigating CCoV. Our findings showed an increase in cell viability, with an improvement of morphological features in CCoV-infected cells at the non-toxic doses of 1 μM for VER and 0.5 μM for PS. In addition, we observed that these compounds caused a strong inhibition in the expression of the aryl hydrocarbon receptor (AhR), a ligand-activated transcription factor which is activated during CCoV infection. Our results also showed the alkalinization of lysosomes in the presence of VER or PS, which may be involved in the observed antiviral activities.